Operationalizing the antecedents and outcomes of union participation in the Indian context. Issue 4 (14th April 2020) - Chawla, Ginni; Singh, Tripti; Singh, Rupali
Abstract : Purpose: Unions and organizations interests are often seen to be in competition. However, union-voice hypothesis suggests that unions can provide a distinctive mechanism to lower organizational costs by reducing exit behavior, absence from work and conflict levels at work. This study aims to look at union participation as a form of voice which is affected by a number of antecedents and in turn has an effect upon the workers performance (i.e. worker behavior effectiveness [WBE]) in an organization. Design/methodology/approach: The study draws on data from 340 permanent labors working in 19 manufacturing units across different regions of India to explore both the antecedents and outcomes of union participation. Hypotheses are tested using mediation analysis. Findings: Results indicate statistically significant relationships between union participation, its antecedents and WBE, with union participation partially influencing the relationship between the constructs. Originality/value: Uniqueness of the study lies in its findings which report positive relationship among union participation, its antecedents and behavior effectiveness. Contrary to the traditional belief that unions are detrimental to the health of any organization, the study suggests that workers decision to join and participate in unions should be viewed positively because only if a person is willing to stay with the organization, he/she seeks to resolve the issues/problems through collective mechanism of union participation and which in turn leads to enhanced performance, reduced absenteeism at the workplace.